Characterisation of microsatellite loci in two species of lice, Polyplax serrata (Phthiraptera: Anoplura: Polyplacidae) and Myrsidea nesomimi (Phthiraptera: Amblycera: Menoponidae) - Martinu, Jana; Roubova, Veronika; Novakova, Milena; Smith, Vincent S; Hypsa, Vaclav; Stefka, Jan (Folia parasitologica, 2015)
Polymorphic microsatellite loci were characterised for two louse species, the anopluran Polyplax serrata Burmeister, 1839, parasitising Eurasian field mice of the genus Apodemus Kaup, and the amblyceran Myrsidea nesomimi Palma et Price, 2010, found on mocking birds endemic to the Galápagos Islands. Evolutionary histories of the two parasites show complex patterns influenced both by their geographic distribution and through coevolution with their respective hosts, which renders them prospective evolutionary models. In P. serrata, 16 polymorphic loci were characterised and screened across 72 individuals from four European populations that belong to two sympatric mitochondrial lineages differing in their breadth of host-specificity. In M. nesomimi, 66 individuals from three island populations and two host species were genotyped for 15 polymorphic loci. The observed heterozygosity varied from 0.05 to 0.9 in P. serrata and from 0.0 to 0.96 in M. nesomimi. Deviations from the Hardy-Weinberg equilibrium were frequently observed in the populations of both parasites. Fst distances between tested populations correspond with previous phylogenetic data, suggesting the microsatellite loci are an informative resource for ecological and evolutionary studies of the two parasites.
Keywords: ectoparasite; Galápagos; Myrsidea; Polyplax; population genetics; evolution; Europe; coevolution